"We for She": Mobilising men and women to act in solidarity for gender equality. (August 2018) - Subašić, Emina; Hardacre, Stephanie; Elton, Benjamin; Branscombe, Nyla R.; Ryan, Michelle K.; Reynolds, Katherine J.
Gender (in)equality is typically studied as a women's issue to be addressed via systemic measures (e.g., government policy). As such, research focusing on mobilising men (and women) towards achieving gender equality is rare. In contrast, this paper examines the mobilisation of both men and women towards gender equality as common cause. Experiment 1 shows that men's collective action intentions increase after reading messages that position men as agents of change towards gender equality, compared to messages that frame this issue as stemming from inadequate government policy. Experiments 2 and 3 demonstrate that messages framing gender equality as an issue for both men and women increase men's collective action intentions, compared to when gender inequality is framed as primarily concerning women. However, this effect emerges primarily under conditions where the source of message is male (Experiment 3). Practical and theoretical implications for mobilising political solidarity in gender equality contexts are discussed.